Fostering Unity in Diversity Through Pancasila-Based Islamic Education Among Madrasah Students - Achmad Muzammil Alfan Nasrullah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study explores the critical role of Pancasila-based Islamic education in promoting tolerance and unity among madrasah students from diverse ethnical backgrounds. Conducted at Madrasah Aliyah Al-Islamiyah 1 Sumber Batu Pamekasan, this qualitative case study examines how integrating Pancasila values with Islamic teachings creates an educational environment that celebrates diversity while maintaining religious identity. Data were collected through in-depth semi-structured interviews with 12 teachers of Islamic studies and general subjects, 24 students from grades 10-12 representing various ethnic and family backgrounds, 4 administrative leaders, and 3 parents; classroom observations totaling 80 hours; and document analysis of curriculum materials, lesson plans, and institutional policies. Data were analyzed using thematic analysis procedures that combined inductive and deductive approaches, including familiarization with the data, generating initial codes, searching for themes, reviewing themes, and defining themes. The findings demonstrate that when Islamic educational principles are harmoniously integrated with Pancasila values, students develop enhanced tolerance, critical thinking about diversity, and commitment to social harmony. This study contributes to the discourse on multicultural education in predominantly Muslim contexts and offers practical implications for educational policy and practice in diverse societies.